2020
DOI: 10.1093/jac/dkaa385
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of concomitant piperacillin/tazobactam and teicoplanin compared with monotherapy

Abstract: Objectives Piperacillin/tazobactam combined with vancomycin has been associated with a decline in renal function when compared with monotherapy. Teicoplanin is a glycopeptide similar to vancomycin. We investigated whether piperacillin/tazobactam combined with teicoplanin is associated with a decline in renal function as well. Methods We conducted a single-centre retrospective cohort study with data from our electronic health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…A previous study indicated that co-administered β-lactam might play an important role in the development of nephrotoxicity associated with teicoplanin. 30 Unfortunately, the present meta-analysis comprised a small number of studies that included patients who had received potential nephrotoxic medications such as piperacillin-tazobactam, aminoglycosides, and calcineurin inhibitors. [31][32][33] Therefore, we could not conduct a meta-regression analysis of these medications.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that co-administered β-lactam might play an important role in the development of nephrotoxicity associated with teicoplanin. 30 Unfortunately, the present meta-analysis comprised a small number of studies that included patients who had received potential nephrotoxic medications such as piperacillin-tazobactam, aminoglycosides, and calcineurin inhibitors. [31][32][33] Therefore, we could not conduct a meta-regression analysis of these medications.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention group in this study showed significantly less nephrotoxicity, which was also observed in the intervention group that only involved patients who replaced VCM with teicoplanin (hazard ratio = 0.460). Recent studies have demonstrated an allowable risk of nephrotoxicity with the teicoplanin and TAZ/PIPC combination but have not reported any outcomes regarding treatment ( 16 , 17 ). Moreover, we have provided the survival rate on day 30 in the entire intervention group, while that in the limited intervention group using teicoplanin (35 patients) was 0.960 (95% CI, 0.836 to 1.102).…”
Section: Discussionmentioning
confidence: 99%
“…Dabei ist zu bedenken, dass die Bestimmung von Teicoplanin-Talspiegeln bei schweren Infektionen erfolgen soll aber bislang in vielen Kliniken noch nicht in gleichem Maße verfügbar ist [68][69][70][71]. Außerdem ist zu beachten, dass Methicillin-resistente Koagulase-negative Staphylokokken (insbesondere S. haemolyticus) im Vergleich zu Vancomycin eingeschränkt Teicoplanin-sensibel sind [72] und Resistenzraten von 5-13 % vorliegen [73][74][75] ßenordnung aber als klinisch nicht relevant [76]. In einer retrospektiven Studie von Aslan et al ergab der Vergleich der AKI-Rate zwischen P/T + V und P/T + Teicoplanin eine signifikant höhere AKI-Rate in der Patientengruppe, die P/T + V erhielten.…”
Section: Alternativen Zu Vancomycinunclassified